Structural-Parameter-Based Jumping-Height-and-Distance Adjustment and Obstacle Sensing of a Bio-Inspired Jumping Robot. (5th June 2015) - Zhang, Jun; Yang, Xi; Song, Guangming; Zhang, Ying; Fei, Shumin; Song, Aiguo
Jumping-height-and-distance (JHD) active adjustment capability is important for jumping robots to overcome different sizes of obstacle. This paper proposes a new structural-parameter-based JHD active adjustment approach for our previous jumping robot. First, the JHD adjustments, modifying the lengths of different legs of the robot, are modelled and simulated. Then, three mechanisms for leg-length adjustment are proposed and compared, and the screw-and-nut mechanism is selected. And for adjusting of different structural-parameters using this mechanism, the one with the best JHD adjusting performance and the lowest mechanical complexity is adopted. Thirdly, an obstacle-distance-and-height (ODH) detection method using only one infrared sensor is designed. Finally, the performances of the proposed methods are tested. Experimental results show that the jumping-height-and-distance adjustable ranges are 0.11 m and 0.96 m, respectively, which validates the effectiveness of the proposed JHD adjustment method.